Scaled RTLS BRDF model extended to high zenith angles - Alexei Lyapustin; Yujie Wang; Sergey Korkin; Crystal Schaaf; Weile Wang; Zhuosen Wang (Frontiers in Remote Sensing)
The Ross-Thick Li-Sparse (RTLS) model provides a good description of the surface bidirectional reflectance distribution function (BRDF) for zenith angles (ZA) up to ∼60°–70°. At higher zenith angles, the behaviour of the RTLS model is not well constrained. This becomes a limiting factor for the processing of geostationary satellite data covering the full range of solar and view zenith angles. Here, we propose a scaled sRTLS model extending the zenith angle range to ∼80°–84° and demonstrate an improved performance based on examples from the processing of GOES-16 ABI data using MAIAC algorithm.